Libya and lessons from Iraq: international law and the use of force by the United Kingdom - White, Nigel D. (Cambridge University Press, 2011)
Those countries, including the United Kingdom, using force in Libya in 2011 have taken much greater care to ensure that their actions are underpinned by legality. This suggests a return to respect for the jus ad bellum, but as the operation against Libya unfolded it became clearer that some of the problems that undermined the legality and legitimacy of the invasion of Iraq 8 years earlier had not been avoided, which raises the question of how such operations can be kept within the strict bounds of the law.